Hunger Crisis in Africa: An In-depth Analysis - Elon Chaka (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2023)
This scientific journal article provides a comprehensive examination of the pervasive issue of hunger in the African continent. Despite its abundant natural resources, Africa continues to grapple with chronic food insecurity and malnutrition, affecting millions of lives. This article investigates the intricate web of factors responsible for the hunger crisis in Africa, analyzes its far-reaching consequences, and proposes a set of practical solutions to alleviate this persistent challenge. Drawing on an extensive array of scholarly sources and empirical data, this research contributes to a deeper understanding of the issue and underscores the urgent need for concerted global efforts to eradicate hunger in Africa.